PENERAPAN SANKSI PIDANA TERHADAP TINDAK PIDANA PEMBALAKAN LIAR DI KECAMATAN BUKIT BATU KABUPATEN BENGKALIS - Sulandari, Devina; Erdianto, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Illegal logging is a forbidden violates laws and regulations, namely in the form of wood theft in state forest areas or private forests and or permit holders to cut more than the ration specified in the permit. There are many problems and factors that cause major problems in forest management. However, no one can argue that the practice of illegal logging is a crime that has damaged the basic formulation of sustainable forest management. Even what has been noticed is that the illegal logging malpractice has become a system of destruction of resources forest that is fast, systematic, and even purportedly organized.How is it not systematic and organized, if the perpetrators are high-ranking officials, members of the TNI, and not a few members of the National Police. This results in a lack of strict law enforcement against illegal loggers. Therefore, to conduct this research, the researcher uses a sociological juridical research method that is descriptive analytical in nature.From this research the results show, namely: First, illegal logging is a practice of organized crime. Data shows that the perpetrators of illegal logging involve law enforcement. This is what makes constraint and obstacles in the process of law enforcement.Second, the current Forestry Law does not explicitly discuss law enforcement over illegal logging. This can be seen in Article 78 of Law Number 41 Year 1999 concerning Forestry, which shows that sanctions against illegal loggers are still not strict, because there are no minimum sanctions.Third, the ecological impact of illegal deluge, landslides, and depletion of water supplies around the forest area. Not a few lives were lost due to deforestation which caused floods and landslides.Keywords:Implementation-Criminal-Sanctions-IllegalLogging